Maternal and Perinatal Outcomes Among Pregnancies Complicated by Isolated Oligohydramnios Compared with Normal Amniotic Fluid Index - Shrestha, Ramesh; Uprety, DK; Thakur, A (Nepal Journal of Obstetrics and Gynaecology, 2017)
Aims: The study was aimed to compare the maternal and perinatal outcomes among pregnancies with isolated oligohydramnios compared to normal amniotic fluid volume between 37-42 weeks. Methods: It was a prospective cohort study done among the singleton pregnancies between 37-42 weeks with isolated oligohydramnios taken as cases (n=100) and pregnancies with normal levels of amniotic fluid matched to cases by gestational age and parity in 2:1 ratio fulfilling the inclusion criteria were taken as controls (n=200). Both the mother and baby were followed up till discharge for outcomes. Results: Majority of the patients (n=300) were of age group 20-30 years (79.0%). Most of them (n=300) were primigravida (74.0%). The overall caesarean section rate was 24.66% (n=300). In the oligohydramnios group, 43.0% had undergone induction of labour (p value<0.05), 63.0% had undergone caesarean section (p value=0.001) and the most common indication for caesarean section was non-reassuring NST (44.44%) (p value<0.05). 26.0% babies had low birth weight, 12% had birth defects, 10.0% were small for gestational age (p value<0.05). There were significantly more ICU admission (13.0% vs 3.5%), early neonatal death (6.0% vs 1.5%), fetal distress (6.0% vs 1.5%) in the oligohydramnios compared to control group ( p value<0.05). Conclusions: Patients with oligohydramnios have increased labour induction, increased operative interferences and increased neonatal mortality and morbidity compared to patients with normal fluid volume.